Development of Nursing Clinical Supervision Application - Ernawati, Ernawati; Damayantie, Netha; Mursidahdewi, Mursidahdewi; Muliyadi, Muliyadi (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
ABSTRACT Nursing services require an effective and efficient nursing management system, so that nursing resources can be directed to produce quality nursing services, one of which is through nursing supervision. Supervision is a personal observation of functions or activities, in the nursing care process, and delegations of functions or activities to maintain accountability and evaluate nursing care appropriately. This research aims to develop a clinical supervision application to improve the quality of implementation of nursing supervision in Jambi city hospitals. Clinical supervision research is designed with an application as guidance and information for room heads, team leaders, and implementing nurses in carrying out clinical supervision so that it can improve the quality of nursing supervision in hospitals. Research design with a mixed methods approach, namely qualitative research on conceptual development and quantitative research used in the product development and testing phases. The research procedure uses analysis-design & development-formative evaluation steps with the Dick and Carey procedure. The research was carried out in three hospitals in Jambi City, namely Abdul Manap Hospital, Bratanata Hospital, and Bhayangkara Hospital Jambi in April - August 2023 with the research subjects being all room heads totaling 16 people and team leaders totaling 24 people. There is a difference in user knowledge about nursing supervision before and after the development of the Android-based clinical nursing supervision educational application with a p-value of 0.000 < 0.005. The model for developing nursing clinical supervision applications using the Dick and Carey learning design approach is a systematic learning design model for developing effective and efficient learning programs. Nursing clinical supervision educational applications can be applied in hospitals by room heads in carrying out supervision in inpatient rooms. Keywords: Development, education, clinical supervision, nursing